Overexpression of MdATG18a in apple improves resistance to Diplocarpon mali infection by enhancing antioxidant activity and salicylic acid levels. Issue 1 (December 2018) - Sun, Xun; Huo, Liuqing; Jia, Xin; Che, Runmin; Gong, Xiaoqing; Wang, Ping; Ma, Fengwang
Abstract Marssonina apple blotch, caused byDiplocarpon mali, is one of the most serious diseases of apple. Autophagy plays a key role in pathogen resistance. We previously showed that MdATG18a has a positive influence on drought tolerance. Herein, we describe how overexpression (OE) ofMdATG18a enhances resistance toD. mali infection, probably because less H2 O2 but more salicylic acid (SA) is accumulated in the leaves of OE apple plants. Expression ofchitinase, β-1, 3-glucanase, and SA-related marker genes was induced more strongly byD. mali in OE lines. Transcript levels of other importantMdATG genes were also drastically increased byD. mali in OE plants, which indicated increased autophagy activities. Taken together, these results demonstrate that OE ofMdATG18a enhances resistance to infection byD. mali and plays positive roles in H2 O2 -scavenging and SA accumulations. Our findings provide important information for designing strategies which could induce autophagy to minimize the impact of this disease on apple production. Improving resistance to apple blotch disease Apple plants that express high levels of a gene involved in the destruction of damaged and redundant cell components demonstrate improved resistance to a serious fungal infection. Fengwang Ma and colleagues of China's Northwest A&F University in Shaanxi examined the effect of overexpressing the geneMdATG18a onDiplocarpon mali fungal infection in apple plants. This gene was previously found to promote drought tolerance in apple plants and is known for its involvement in autophagy, an immune response to infection that removes damaged cell organelles. The researchers found that plants overexpressingMdATG18a were more resistant to developing Marssonina apple blotch disease compared to wild apple plants, most likely due to improvements in autophagy activity. The team concludes that strategies designed to induce autophagy could improve apple resistance to fungal infection.